2019
DOI: 10.3390/antiox8060152
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenol Intake, Blood Pressure, and Hypertension: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background: Dietary polyphenols, including flavonoids, have been the focus of major recent attentions due to their wide content in a variety of foods commonly consumed and the findings from numerous studies showing evidence of an association with positive outcomes on human health. Methods: A systematic search using electronic databases PubMed and EMBASE was performed to retrieve English language studies published from the earliest indexing year of each database to April 2019, reporting on the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 86 publications
1
79
1
1
Order By: Relevance
“…Additionally, lignans have been demonstrated to exert anti-oxidative and anti-inflammatory properties in neurons and protect the blood-brain barrier against inflammatory cells by reducing oxidative stress, inflammation and permeability [66][67][68]. Dietary (poly)phenols may ameliorate poor endothelial function [69] and help to control blood pressure [70], which, in turn, has been associated with measures of sleep quality together with decreases in the percentage of REM sleep and increases in REM sleep latency [71][72][73]. Previous epidemiological studies have shown an inverse association between the intake of specific classes of (poly)phenol (in line with the findings shown in the present study)-including flavones and flavanones among flavonoids [74], and hydroxycinnamic acids-and the occurrence of hypertension [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lignans have been demonstrated to exert anti-oxidative and anti-inflammatory properties in neurons and protect the blood-brain barrier against inflammatory cells by reducing oxidative stress, inflammation and permeability [66][67][68]. Dietary (poly)phenols may ameliorate poor endothelial function [69] and help to control blood pressure [70], which, in turn, has been associated with measures of sleep quality together with decreases in the percentage of REM sleep and increases in REM sleep latency [71][72][73]. Previous epidemiological studies have shown an inverse association between the intake of specific classes of (poly)phenol (in line with the findings shown in the present study)-including flavones and flavanones among flavonoids [74], and hydroxycinnamic acids-and the occurrence of hypertension [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and clinical studies suggest that an anthocyanin-enriched diet may lower levels of certain oxidative stress biomarkers in humans, and this could be associated with reduced risk of cognitive decline and the development of neurodegenerative and cardiovascular diseases, as well as having sustained hepatic function and kidney protecting activities [12,[104][105][106][107][108][109][110][111][112][113][114][115].…”
Section: Biological Effects Related To the Antioxidant Activity Of Anmentioning
confidence: 99%
“…Polyphenols are bioactive molecules that are present in plant-based foods. Dietary intake of plant polyphenols has been associated with several health outcomes related to oxidative stress, including cardiovascular diseases [20], hypertension [21], diabetes [22], mortality [23], and some cancers [24]. The main ingredients of mulberry leaf polyphenol extract (MLPE), such as quercetin, can inhibit the progress of numerous human cancers [25].…”
Section: Introductionmentioning
confidence: 99%